Demonstrating Improved Surgical Communication and HAndoveR Generates Earlier Discharges (DISCHARGED). Issue 3 (September 2018) - Dean, Jonathon; Phillips, Georgina; Turner, Warren; Refson, Jonathan
Abstract : Background: Weekend surgical handover at the Princess Alexandra Hospital NHS Trust in Harlow, Essex, did not fully comply with Royal College of Surgeons England guidelines. Out-of-hours care is under increased scrutiny, and we implemented a quality improvement intervention of a mandatory, standardized weekend handover form to streamline weekend care. This was shown to increase discharges and decrease lengths of stay for patients whose hospital stay included a weekend. Methods: Data were collected for 15-week preimplementation and postimplementation. The number of patients handed over for senior weekend review was recorded, and for each, the presence or absence of a working diagnosis, relevant investigations, a management plan, and any outstanding tasks was recorded. A standardized weekend handover form was implemented, and these criteria as well numbers of discharges and lengths of stay were compared. Results: An average of 32 patients was handed over each weekend before and after implementation. The average number of handovers with a listed working diagnosis (19.20 to 30.80, Δ11.60, P < 0.0001), management plan (16.40 to 31.73, Δ15.33, P < 0.0001), and tasks (16.60 to 29.13, Δ12.53, P < 0.0001) significantly increased. Average weekend discharges increased (39.07 to 48.93, Δ9.86, P = 0.0034). Average lengths of stay for emergency patients whose stays included a weekend shortened by 1.96 days (11.11 to 9.15 days, Δ−1.96, P = 0.0192) in keeping with the length of a weekend, with estimated annual cost-savings of between £740 000 and £3.82 million. Conclusions: Implementation of a standardized weekend handover form resulted in an increase in compliance to national guidelines as well as an increase in weekend discharges and decreased length of stay for emergency patients with significant cost-savings.